SPE Western Regional/Aapg Pacific Section Joint Meeting 2002
DOI: 10.2118/76727-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Water Saturation on Spontaneous Water Imbibition

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe effect of initial water saturation on gas recovery by cocurrent spontaneous water imbibition and imbibition rate was investigated both theoretically and experimentally. Equations correlating initial water saturation, gas recovery, imbibition rate, rock/fluid properties, and imbibition time were derived and used to conduct the theoretical analysis. These equations foresee that gas recovery and imbibition rate could increase, remain unchanged, or decrease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…Li et al (2002) did water-gas COCSI tests on Berea sandstone at different initial water saturations. The final gas recovery decreased with increase in the initial water saturations.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Li et al (2002) did water-gas COCSI tests on Berea sandstone at different initial water saturations. The final gas recovery decreased with increase in the initial water saturations.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…They also tested the effect of initial water saturation on the performance and observed that the existence of initial water saturation causes higher ultimate recovery from the surfactant solution imbibition. The existence (Weisbord et al, 2002;Babadagli, 2003c) and amount (Li et al, 2002) of initial water saturation are critical on the recovery and there would be considerable amount of water left from primary and secondary recovery applications in the matrix. These observations showed that additional recovery with surfactant solutions is a possibility after completed imbibition recovery with brine.…”
Section: Fractured Rocksmentioning
confidence: 99%
“…Several researchers [19][20][21] have observed that recovery for fixed volumes of water increases in a manner that is proportional to t . In capillary-driven processes, recovery is due to imbibition.…”
Section: Imbibitionmentioning
confidence: 99%